Fatal Lactic Acidosis in a Kidney Transplant Recipient on Combination Antiretroviral Therapy after Initiation of Tacrolimus Therapy. (5th January 2012) - Holmes, Michael V.; Kulasegaram, Ranjababu; Lucas, Sebastian B.; Wong, Terry; Hilton, Rachel
Abstract : In general, kidney transplantation is safe and efficacious in patients receiving treatment for HIV. Although multiple drug interactions between antiviral and immunosuppressive treatments exist, few patients experience serious adverse reactions. We report a case of fatal lactic acidosis in a healthy kidney transplant recipient with stable HIV infection who had previously received treatment for and cleared hepatitis C virus infection. Death occurred less than one month following the initiation of tacrolimus therapy. Based on predicted drug interactions, appropriate tacrolimus dosing was calculated prior to its commencement, yet plasma tacrolimus levels were initially unexpectedly high. The patient subsequently developed lactic acidosis and hepatic steatosis, presumably due to mitochondrial toxicity from the antiretroviral regimen on which he had previously been stable. We suspect CYP2C19 * 2 (poor metaboliser) genotype status and concomitant treatment with lansoprazole, tacrolimus, and antiretroviral (ARV) medications resulted in hepatic decompensation. This highlights the importance of careful interaction screening for all new drugs administered to patients with HIV who have complex treatment regimens as well as heightened clinical vigilance for unexpected toxicities.